2011
DOI: 10.1007/s00170-011-3565-2
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on ball end milling of P20 die steel with cutter orientation

Abstract: The generation mechanism of machininginduced residual stresses is a complex nonlinear and thermal-mechanical coupling problem. The cutting forces and cutting temperature produced in machining process must be considered simultaneously. The influence of cutter orientation and feed per tooth on the cutting speed, cutting forces, cutting temperature, and residual stresses is discussed in the present study. Effective cutting speed in accordance with the inclination angle in feed direction is analyzed. The cutting f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…In turn, the growth of rotational speed causes the reduction of cutting time and simultaneously an increase of the material removal rate. However, in this cutting mode, cutting forces are usually higher than those obtained during milling with α>0 [22,7] and hence the quality of the machined surface is reduced. Thus, the surface inclination angle during ball end milling of free form surfaces should be optimized to minimise cutting forces and maximise material removal rate.…”
Section: The Determination Of Materials Removal Ratementioning
confidence: 99%
See 1 more Smart Citation
“…In turn, the growth of rotational speed causes the reduction of cutting time and simultaneously an increase of the material removal rate. However, in this cutting mode, cutting forces are usually higher than those obtained during milling with α>0 [22,7] and hence the quality of the machined surface is reduced. Thus, the surface inclination angle during ball end milling of free form surfaces should be optimized to minimise cutting forces and maximise material removal rate.…”
Section: The Determination Of Materials Removal Ratementioning
confidence: 99%
“…According to Rybicki [21], an increase in surface inclination angle from 10° up to 60°, during ball end milling with constant cutting speed mode, resulted in an approximately 55% increase in cutting time. In addition, Chen et al [22] have shown that surface inclination angle has a significant influence on the cutting forces, due to variations in edge force values along the length of the cutting edge. Therefore, reliable optimisation of the ball end milling with variable surface inclinations should focus both on cutting forces and process efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…The properties are detailed in Table 1. 11, 29 P20 die steel is considered for the experiments because of its availability, machinability and resilience during the die casting and micro-injection moulding processes.…”
Section: Experimentationmentioning
confidence: 99%
“…damping, stiffness) of machine-toolholder-tool system [8 ,9]. Moreover, in case of a ball end milling process, the variations of surface inclination angle along the toolpath cause the changes in tool's effective cutting speed and thus significantly affect the process dynamics [10]. Therefore, the identification of the crucial factors influencing the tool's instantaneous displacements during milling is important in terms of machined surface quality improvement.…”
Section: Introductionmentioning
confidence: 99%